Escalating the employee organisational commitment through employee job satisfaction: A Malaysian childcare centre perspective - Sulaiman, Yaty; Othman, Abdul Rahim; Perumal, Selvan (2015)
The number of childcare centers in Malaysia has been steadily increasing and is expected to continue to increase in the future.This is largely due to the active campaign of the Malaysian Government for early childhood education, which is based on the important role played by formal early childhood education.One major factor contributing to the success of childcare centre is the quality of the childcarers or the front-line employees. Hence, a quality childcare service is impossible without quality childcare employees.In fact, Malaysian childcare centers experience a high job turnover rate among their front-line employees. The high turnover rates could be due to lower employee job satisfaction levels which lead to a lower employee organisational commitment levels among the childcare employees.Finally, the study presents some suggestions for further studies that can be conducted in the future.